The consequences of pain in early life: injury-induced plasticity in developing pain pathways - Schwaller, Fred; Fitzgerald, Maria (The European journal of neuroscience, 2014)
Pain in infancy influences pain reactivity in later life, but how and why this occurs is poorly understood. Here we review the evidence for developmental plasticity of nociceptive pathways in animal models and discuss the peripheral and central mechanisms that underlie this plasticity. Adults who have experienced neonatal injury display increased pain and injury‐induced hyperalgesia in the affected region but mild injury can also induce widespread baseline hyposensitivity across the rest of the body surface, suggesting the involvement of several underlying mechanisms, depending upon the type of early life experience. Peripheral nerve sprouting and dorsal horn central sensitization, disinhibition and neuroimmune priming are discussed in relation to the increased pain and hyperalgesia, while altered descending pain control systems driven, in part, by changes in the stress/HPA axis are discussed in relation to the widespread hypoalgesia. Finally, it is proposed that the endocannabinoid system deserves further attention in the search for mechanisms underlying injury‐induced changes in pain processing in infants and children. Pain in infancy influences pain reactivity in later life, but how and why this occurs is poorly understood. Here we review the evidence for developmental plasticity of nociceptive pathways in animal models and discuss the peripheral and central mechanisms that underlie this plasticity.